Multi-fidelity progressive damage simulation of notched composite laminates with various ply thicknesses. (1st May 2022) - Higuchi, R.; Aoki, R.; Onodera, S.; Lu, X.; Zhi, J.; Leong, K.H.; Yokozeki, T.; Okabe, T.; Tay, T.E.
Abstract: In this study, a multi-fidelity fracture simulation scheme of composite laminates that accomplishes a seamless transition between medium- and high-fidelity crack models, namely, smeared crack models (SCMs) and discrete crack models (DCMs), is developed. The proposed scheme is based on the adaptive discrete-smeared crack (A-DiSC) method and a theoretical model for saturated crack density. The A-DiSC method first employs a DCM to model the transverse cracks in the laminates. If the crack density of each ply reaches the saturation value calculated using the theoretical model, the DCM is converted to an SCM. At this point, some cracks that are longer than a certain critical length remain explicitly modeled by the DCM, as they can significantly affect the subsequent path to final failure. By combining the two models, this method reduces the computational cost while preserving a sufficient prediction accuracy particularly in the case with numerous noncritical cracks up to failure. A simulation of the open-hole tensile test of composite laminates with various ply thicknesses was performed to verify the prediction accuracy of the developed scheme, and the predicted results were compared with the experimental results.